Selection of Manufacturing Process for Automotive Bumper Fascia Using Analytical Hierarchy Process - A, hambali; L.I, Intan; A.A, Tajul; A.R, Soufhwee; Roni Sahroni, Taufik (Universiti Teknikal Malaysia Melaka, 2012)
This paper presents a way of determining the most appropriate process for automotive bumper fascia using analytical hierarchy process (AHP) at the early stage of the product development process. AHP is a method that assists decision makers to determine the right decision by considering various factors influencing the selection process. There are 5 types of processes under consideration are injection moulding (IM), vacuum thermoforming, reaction injection moulding (RIM), compression moulding (CM), and blow moulding (BM). The analysis ranks the 5 types of processes for suitability of use in manufacturing automotive bumper fascia based on 6 main selection factors and 12 sub-factors. Determining the right manufacturing process was performed based on the AHP concept through the 9 steps. The results indicated that the vacuum forming was the most appropriate manufacturing process because it has the highest value (23.99%) among the other manufacturing processes. This result is also supported by MindDecider software where the vacuum forming was selected as a first choice.